The sovereign trickster : death and laughter in the age of Duterte - Rafael, Vicente L. (Duke University Press, 2022)
"Vicente L. Rafael provides a complex account of how Philippine president Rodrigo Duterte uses humor, fear, misogyny, and violence to weaponize death as a means to control life."--